The Microfoundations of Macroeconomics: An Evolutionary Perspective - Jeroen C.J.M. van den Bergh; John M. Gowdy (Tinbergen Institute, 2000)
We consider the microfoundations controversy from the perspective ofeconomic evolution and show that the debatecan benefit from lessons learned in evolutionary biology. Althoughthe analogy between biology and economics hasbeen noted before, it has rarely focused on clarifying the micro-macro distinction in economic theory and modelling.The macroevolution controversy in biology has generated testabletheories such as the existence of punctuatedequilibria in evolutionary history, the distinction between selectionand sorting, and group selection. The micro-macrodebate is further developed in biology than in economics due to agreater degree of specialisation and interaction ofvarious sub-disciplines. The task for economists is to distinguishbetween insights directly relevant for economic theoryand ones that hinge on unique features of biological systems. Weargue that both micro and macro processes driveeconomic change and that macroeconomic change cannot be explained bymicro level optimising alone. We show thatdebates in biology about group selection and punctuated equilibriaare directly relevant to understanding economicevolution. The distinction between reductionism and holism is oflittle use and in its place a hierarchical approach isproposed. This allows for both upward and downward causation andinteraction between levels. Specific topicsincorporating ideas from evolutionary theory into economics are:economic exaptations, macroeconomic consequencesof institutions, and group selection. Two insights are: selection(sorting) can occur at levels above the individual firm;and, macroeconomic theories can be formulated without reference tofirm level descriptions. Micro and macroapproaches to economic change are complementary.
Keywords: 330; Makroökonomik; Mikroökonomische Fundierung; Evolutionsökonomik; Theorie